2020
DOI: 10.1039/d0tc00388c
|View full text |Cite
|
Sign up to set email alerts
|

The role of self-assembled monolayers in electronic devices

Abstract: Today, the self-assembled monolayer (SAM) approach for surface functionalization is regarded as highly versatile and compelling, especially in the immobilization of biomolecules and fabrication of novel supramolecular architectures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
136
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 169 publications
(136 citation statements)
references
References 134 publications
(175 reference statements)
0
136
0
Order By: Relevance
“…In self‐assembled monolayer approach, the concentration of SAM molecules plays very crucial role as both low and high concentrations can hinder the formation of ordered assembly and its reactivity. [ 3 ] Thus, the selection of SAM solution concentration is one of the most important parameter in order to form a highly ordered monolayer with minimal disorder and high reactivity to external species such as the analyte to be detected or biomolecules to be immobilized on the SAMs.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…In self‐assembled monolayer approach, the concentration of SAM molecules plays very crucial role as both low and high concentrations can hinder the formation of ordered assembly and its reactivity. [ 3 ] Thus, the selection of SAM solution concentration is one of the most important parameter in order to form a highly ordered monolayer with minimal disorder and high reactivity to external species such as the analyte to be detected or biomolecules to be immobilized on the SAMs.…”
Section: Resultsmentioning
confidence: 99%
“…It has been found that the process of silanization requires the sufficient amount of water during the hydrolysis process; however both the excess and deficiency of water can hinder the monolayer formation. [ 3 ] In silanization process, the APTMS molecules immediately attack OH groups present on the surface (ZnO NWs in present case) and undergo hydrolysis by consuming the sufficient amount of water, which results into the formation of monolayer. As the reaction proceeds, the water molecules becomes resistive toward the surface due to the formation of monolayer on it and start reacting with the SAM molecules in the solution instead.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…2D monolayer organic crystals are usually fabricated by solution‐processed methods at water/air interface, [ 14–22 ] where water surface is usually used to control the diffusion of organic solvent and serves as a substrate for the self‐assembly of organic molecules due to its relatively high surface tension and molecularly flat surface. Langmuir–Blodgett (LB) technique has been previously applied for the fast and simple fabrication of organic monolayer crystals at water/air interface.…”
Section: Figurementioning
confidence: 99%